Pengaruh Customer Relationship Management dan Kualitas Layanan Terhadap Kepuasan Konsumen Toko Emas Karunia Jaya - Dunan, Hendri; Saputra, Adean (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine and explain the influence of customer relationship management and service quality on consumer satisfaction at the Grace Jaya Gold Shop. This research uses a quantitative survey approach. The population in this study were all Instagram followers of the Grace Jaya Gold Shop. The sample used in this research was 83 respondents taken using a population using the Simple Random Sampling technique, because sampling of population members was carried out randomly without paying attention to the strata in the population. With this method the entire population is assumed to have the same opportunity to become the research sample. The data sources in this research are primary data and secondary data. Questionnaire and interview methods were used to obtain the data required for this investigation. Using a Likert Scale is the data collection technique used in this research. The results of the research show that customer relationship management does not have a positive effect on consumer satisfaction at the Grace Jaya Gold Store. Service quality has a positive effect on consumer satisfaction at the Grace Jaya Gold Store.